Spiritual Domain in Resilience Framework - Amalia, Madihie; Salmah, Mohamad Yusoff; Jamayah, Saili; Siti Norazilah, Mohd Said (2017)
The aim of paper is to acknowledge spiritual domain as new domain in the Resilience Framework- The Magic Box Model (Hart, Blincow, & Thomas, 2017). The model has five domains: Basic, Belonging, Learning, Coping, and Core Self. The study was conducted in Malaysia with thirteen to seventeen-year olds, both gender. A Q-sort methodology was employed to collect the data in three selected secondary schools after the permissions obtained from the Ministry of Education Malaysia. The main instrument is the constructed items from the Magic Box Model. The finding shows the existing new domain which is the spiritual domain. The spiritual becomes one of the main domains in resilience development in adolescents, on top of the Belonging domain. The study implies a new scope in resilience studies- spiritual domain in helping adolescents in facing adversity in life, especially in Malaysia and Asia.